Query Performance of CORBA Trading Object Service Using LDAP As Backend Storage - Farkhana, Muchtar (2007)
This research is an initiative towards increasing the performance of trading service in a CORBA environment so that the trader server can provide a fast response when a query is performed. Based on the statement in the trading service specification issued by OMG and past research, the selection of backend storage for the trader server influences the performance of the trading service. Thus, an emphasis on the selection of appropriate solutions is focused on the most suitable backend storage to be used by the trader server in order to improve the query operation in the trading service. Read-optimized storage is the chosen criteria of backend storage for this research as, ultimately, it allows the searching and retrieving process to be improved in the trading service during the query operation. This fact is proven in this research, and the storage chosen as the suggested solution is LDAP. This thesis examines the capability of LDAP in improving the performance of query operation in the trading service in which a performance measurement is conducted to differentiate the performance result obtained from the trading service which uses LDAP as its backend storage, and the trading service that uses relational database as its backend storage. Based on the experiments conducted, we find that the trading service using LDAP shows a better performance as compared to the trading service with the relational database. From the results, it has been further proven that there is an increase in the performance during the query operation in the trading service that uses LDAP as its backend storage.